Case report: Rupture of an ileus tube in a patient with recurrent rectal cancer - Ma, Jun; Jiang, Ye; Zhou, Chaoping; Wang, Datian; Zhao, Chunxia; Zhang, Yaming (Frontiers in Oncology, 2023)
The insertion of an ileus tube is an important treatment for intestinal obstruction.According to previous reports, jejunal intussusception has been reported as a complication associated with ileus tube placement. However, rupture of the weighted tip of an ileus tube has not been reported before. Herein, we report a 55year-old Chinese woman who underwent radical proctectomy (DIXON) for rectal cancer and developed pelvic recurrence and lung metastasis 65 months after surgery, accompanied by symptoms of acute intestinal obstruction. An ileus tube was inserted before the operation (extensive total hysterectomy ， bilateral adnexal placement 删除[非常无语]: , 删除[非常无语]:and its common complication is intestinal intussusception, but not rupture of the tube.